2009
DOI: 10.1111/j.1349-7006.2008.01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of alcohol consumption with polymorphisms in alcohol‐metabolizing enzymes on pancreatic cancer risk in Japanese

Abstract: The putative impact of alcohol on pancreatic cancer (PC) risk remains controversial. Here, we conducted a case-control study in Japanese to assess the impact of alcohol in conjunction with polymorphisms in alcohol-metabolizing enzymes. Cases were 160 patients with pancreatic cancer at Aichi Cancer Center, Nagoya, Japan. Two control groups of 800 age-and sex-matched non-cancer subjects each were independently selected. The impact of alcohol and polymorphisms in aldehyde dehydrogenase 2 (ALDH2) Glu504Lys, alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 34 publications
1
41
2
1
Order By: Relevance
“…1) [14]. The ability of these ALDHs to repress cellular acetaldehyde levels is consistent with a role for ALDHs in colon and pancreatic cancers and is supported strongly by the association of ALDH2 deficiency with high incidence of CRC and pancreatic cancer in heavy ethanol drinkers [15, 16]. In addition to metabolizing acetaldehyde, ALDH1 isozymes are the primary enzymes involved in the metabolism of retinaldehyde to retinoic acid (RA), a signaling molecule that plays a crucial role in cellular proliferation and differentiation [11].…”
Section: Introductionmentioning
confidence: 62%
“…1) [14]. The ability of these ALDHs to repress cellular acetaldehyde levels is consistent with a role for ALDHs in colon and pancreatic cancers and is supported strongly by the association of ALDH2 deficiency with high incidence of CRC and pancreatic cancer in heavy ethanol drinkers [15, 16]. In addition to metabolizing acetaldehyde, ALDH1 isozymes are the primary enzymes involved in the metabolism of retinaldehyde to retinoic acid (RA), a signaling molecule that plays a crucial role in cellular proliferation and differentiation [11].…”
Section: Introductionmentioning
confidence: 62%
“…Daily alcohol consumption (in grams) was determined by totaling the amount of pure alcohol in the average daily consumption of Japanese sake (rice wine), shochu (distilled spirit), beer, wine, and whiskey. The amount of ethanol in each beverage has been described elsewhere (22). The subjects were categorized based on drinking status into the three groups of never, former, and current drinkers.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, the medical background of the controls would remain the potential souse of bias. In this regard, our previous study in women demonstrated that this matter had only limited impact: more than 66% of non-cancer outpatients at ACCH have no specific medical condition, while the remaining 34% have specific diseases such as benign tumors, non-neoplastic polyps or both (13.1%), mastitis (7.5%), gastrointestinal disease (4.1%), or benign gynecologic disease (4.1%) (Kanda et al, 2009;Kawase et al, 2009). The situation for men is thought to be comparable.…”
Section: Discussionmentioning
confidence: 97%